Analysis of Students Learning Concentration in Islami Religious Education at Senior High Schools - Witri Ramadhani (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study aims to analyze the factors that influence students' learning concentration in learning Islamic Religious Education at SMA Negeri 5 Kerinci. The main problem identified is the decline in student concentration due to the influence of internal factors such as interest, motivation, emotions, and physical condition, as well as external factors in the form of learning environment, social interaction, and digital media. The method used was a qualitative approach with interviews, observations, and questionnaires as data collection techniques. The results showed that students' learning concentration is strongly influenced by the interaction between internal and external factors. The role of Islamic education teachers as facilitators, motivators, and emotional regulators has proven effective in improving student concentration. In addition, relevant pedagogical approaches and linking religious values also contribute significantly to students' learning focus. The findings provide important implications for Islamic religious education teaching strategies, namely the need for a combination of interactive methods, emotional management and the application of spiritual values that can improve concentration, engagement and overall learning quality in the future.